A Computer-Supported Framework for Form Analysis - Buthayna Eilouti (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Although there are several frameworks for the synthesis of form, and for the automated development of geometric shapes, studies in the systematic analysis of architectural forms and their automation are still underrepresented. This paper describes a framework for computer-aided geometric form analysis. It illustrates the framework's applicability by an example from precedent architectural design. The form analysis framework is developed theoretically and further translated into a computer code that is written in the AutoLISP language to fit its graphic operation system. Application of the framework and its computerized code demonstrates its power as a promising analytical tool that can help designers analyze precedents' morphological structure more efficiently.